2020
DOI: 10.5897/jmpr2019.6872
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the research of Adenanthera pavonina: From traditional use to intellectual property

Abstract: Adenanthera pavonina, an Asian native leguminous, is a well known highly used plant in traditional medicine. Such broad herbal medicine applications motivated several researchers to study its chemical composition, mainly of its leaves, seeds, and barks, besides the pharmacological effects aiming to demonstrate scientific evidence of its empirical uses. Most studies have been conducted with plant derivatives, and more recent studies have focused on isolated compounds. The phytochemical screening revealed variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…This tree is also known as the red bead tree worldwide. Traditionally, different parts of this plant have been used to treat an extensive range of conditions including hypertension, boils, diabetes, diarrhea, arthritis, cholera, asthma, stomach bleeding, fever, indigestion, epilepsy, vomiting, pulmonary infections, and cancer [1][2][3]. Besides these, bark and leaves are also used as a remedy for ulcers, gout, dysentery, hematemesis, and rheumatism [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tree is also known as the red bead tree worldwide. Traditionally, different parts of this plant have been used to treat an extensive range of conditions including hypertension, boils, diabetes, diarrhea, arthritis, cholera, asthma, stomach bleeding, fever, indigestion, epilepsy, vomiting, pulmonary infections, and cancer [1][2][3]. Besides these, bark and leaves are also used as a remedy for ulcers, gout, dysentery, hematemesis, and rheumatism [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the phytochemical and pharmacological possibilities of various parts of A. pavonina in the past [5][6][7][8]. Pharmacological investigations have shown that different parts of this plant have antinociceptive, anti-inflammatory, analgesic, anti-diarrheal, antimicrobial, antioxidant, anti-hyperglycemic, and hypolipidemic properties [2,7,9]. Phytochemical studies have demonstrated that different parts of this plant contain a wide array of chemical compounds including phenolics, flavonoids, alkaloids, steroids, saponins, triterpenoids, and glycosides [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Adenanthera pavonina (AP) is an important medicinal plant widely distributed in Asia and America. Various parts of AP are traditionally used for the management of various health illnesses such as boils, inflammations, arthritis, rheumatism, blood disorders, cholera, epilepsy, convulsion, paralysis, spasm, indigestion, pulmonary infection, chronic rheumatism, gout, haematuria, haematemesis, ulcer and diarrhea [5]. And also bark of AP have been scientifically evaluated for its anti-inflammatory [6], anticancer [7], antibacterial [8], antifungal [9], anthelmintic [10], antioxidant [11] and antihyperlipidemic activities [12].…”
mentioning
confidence: 99%